Penanaman Pendidikan Karakter Disiplin Dan Tanggung Jawab Melalui Tata Tertib Sekolah (Studi Kasus di SMA Negeri 1 Rembang Tahun Pelajaran 2015/2016) - Saputra, Dimas Kurniawan; , Prof. Dr. Bambang Sumardjoko, M. Pd (2016)
This study aimed to describe the character education of discipline and responsibility through the school rules. This study used a qualitative approach, data collection is done by observation, interviews, and documentation. Test the validity of the data using a triangulation of sources and techniques. The data analysis applying interactive models through data collection, data reduction, data presentation, and conclusion. The results of this study can be concluded that cultivation of character education forms of discipline and responsibility through the school rules during this proved to be quite good, the socialization of school discipline by sticking the school rules in classrooms and all components comply with these rules. Factors inhibiting the cultivation of character education discipline and responsibility through the school rules are planting the character of discipline distance home much and too problematic vehicles, there are students who forgot or lost their attributes, their students are less misunderstandings about the school rules, the student who does not like maple teachers, there occurs a loss of notebooks for the return of the tools and materials. From the planting of character education is the responsibility of the attitude of students who are still lazy, and students are often deliberately arrive late at the time of the turn of the picket, the students who are not interested in these activities, the students do not know propose solving the problems faced in particular. The driving factors for cultivation of character education discipline and responsibility through the school rules is the enforcement of sanctions contained in the school rules, the observation of the school as well as their means of cooperative schools, awarding prizes to those who have never violated. The desire of parents in planting characters discipline and responsibility through the school rules of which there must be monitoring of the schools, the enforcement of sanctions so that students who abuse deterrent and socialization of school rules to students.